Seed-mediated growth of Au core–Pd shell-structured nanoparticles on a polymer nanofibrous mat as a highly active photocatalytic composite material. (October 2020) - Xu, Lin; Wang, Xiao; Ma, Ting; Zhao, Xueyu
Abstract: Photocatalytic technologies have received extensive attention as green catalysts. Here, we successfully designed gold (Au) core–Palladium (Pd) shell-structured nanoparticles (NPs) as a nanoreactor, in which the Pd shell provides the active sites and Au core offers strong plasmonic properties. We then used the seed-mediated growth approach to fabricate the Au core–Pd shell-structured nanoparticles on a polyvinyl alcohol (PVA) nanofibrous mat as a highly active photocatalytic composite material for hydrogenation reactions under room temperature. Our results show that the Au core–Pd shell-structured nanoparticles are more effective in catalyzing the hydrogenation of styrene than the Pd nanoparticles. The photocatalytic experimental results show that the yields of ethylbenzene under light conditions are higher than that under 60 °C in the dark. This shows that the PVA/Au NP/Pd NP composite material can efficiently utilize heat from light to promote catalytic reactions via photothermal effects. The PVA/Au NP/Pd NP composite material not only exhibits a very high photocatalytic efficiency, but can also easily recover from the reaction. The work offers a simple and efficient strategy for recyclable and highly active catalysts for light-driven organic reactions. Graphical abstract: The Au core–Pd shell-structured nanoparticles on a polymer nanofibrous mat are fabricated as a recyclable and highly active photocatalytic composite material for hydrogenation reactions under room temperature. Image 1 Highlights: The Au core/Pd shell nanoparticles on a polymer nanofibrous mat are fabricated via the seed-mediated growth approach. The PVA/Au NP/Pd NP composite material exhibits very high photocatalytic efficiency due to the photothermal effect. The PVA/Au NP/Pd NP composite material is easily recovered from the catalytic reaction.